Automation of a Mattson Bean Cooker: A simple and a low-cost approach - Deroldo Sabadoti, Viviane (2020)
ABSTRACT This work aimed to automate the most popular method to determine the cooking time of grains: the Mattson Bean Cooker apparatus. The proposed system is a low-cost and a simple approach, offering the possibility of calibration according to the size of the analyzed grains. The automation is based on the use of magnets, Hall effect sensors, potentiometers, and an operational amplifier to monitor the plungers' positions. The time required for each grain to be cooked is shown in a LCD display, and the connection among all the components is made by an ATmega328 microcontroller from the Arduino UNO R3 board. The proposed system can be assembled in an already existent device, costing ~US$200. Its validation was made with two different grains: carioca beans (Phaseolus vulgaris) and lentils (Lens culinaris). Despite the differences between sizes, both grains were suitably analyzed with the developed system.